Mazabraud 증후군에서 발생한 골육종으로 악성 변환: 증례 보고 - 박양일; 유지영; 공준석; Yang Il Park; Ji Young Yoo; Joon Seog Kong (Journal of the Korean Society of Radiology, 2021)
Mazabraud syndrome is a rare benign disease that is accompanied by polyostotic fibrous dysplasia and intramuscular myxoma. Malignant transformation of fibrous dysplasia occurs in approximately 1% of cases. To date, only eight cases of malignant transformation, of fibrous dysplasia to osteosarcoma, in Mazabraud syndrome have been reported worldwide. The authors report the first case of osteosarcomatous transformation in a patient with Mazabraud syndrome in the Republic of Korea, focusing on imaging findings. Mazabraud 증후군은 다골성 섬유성 이형성과 근육 내 점액종이 동반되는 매우 드문 양성 질환이다. 섬유성 이형성에서 악성 변환이 일어나는 경우는 약 1%로 알려져 있고, Mazabraud 증후군의 섬유성 이형성에서 발생한 골육종으로 악성 변환에 대한 보고는 아직까지 전 세계에 8예에 불과하다. 저자들은 Mazabraud 증후군 환자에서 섬유성 이형성이 있었던 경골에 골육종이 발생한 증례를 경험하였기에 영상 소견을 중심으로 대한민국에서 처음으로 보고한다.